Editorial Team/Equipe Editorial/ Equipo Editorial 2023/2024 - Antonio Marcos de Oliveira Siqueira; Ivan Carlos Franco (The Journal of Engineering and Exact Sciences)
Editorial Team/Equipe Editorial/ Equipo Editorial 2023/2024